1998
DOI: 10.1088/0264-9381/15/2/013
|View full text |Cite
|
Sign up to set email alerts
|

A fully -dimensional Regge calculus model of the Kasner cosmology

Abstract: Abstract. We describe the first discrete-time 4-dimensional numerical application of Regge calculus. The spacetime is represented as a complex of 4-dimensional simplices, and the geometry interior to each 4-simplex is flat Minkowski spacetime. This simplicial spacetime is constructed so as to be foliated with a one parameter family of spacelike hypersurfaces built of tetrahedra. We implement a novel two-surface initial-data prescription for Regge calculus, and provide the first fully 4-dimensional application … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…These oscillations do not appear to induce instabilities in the numerical evolution of simplicial lattices. Indeed, previous studies have indicated that the oscillations gradually decay as the evolution proceeds [2]. However, M. Miller [8] has reported instabilities arising in linearised Regge calculus on asymmetrical grids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These oscillations do not appear to induce instabilities in the numerical evolution of simplicial lattices. Indeed, previous studies have indicated that the oscillations gradually decay as the evolution proceeds [2]. However, M. Miller [8] has reported instabilities arising in linearised Regge calculus on asymmetrical grids.…”
Section: Resultsmentioning
confidence: 99%
“…In this section we solve the Regge equations for the vacuum Kasner cosmology using a (3 + 1)-dimensional formulation of Regge calculus described elsewhere [2]. The initial value problem is solved and the lattice is evolved subject to simplicial lapse and shift conditions.…”
Section: Numerical Solution Of the Regge Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts have been made to adapt the ADM 3+1 equations to the Regge calculus [11,12] but progress has been slow. A much more promising scheme, for the Regge calculus, is due to Sorkin [13] with later development by Barrett et al [14] and Gentle and Miller [15].…”
Section: Introductionmentioning
confidence: 99%